2009
DOI: 10.1016/j.dnarep.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of APE1 in differentiated neuroblastoma SH-SY5Y cells in response to oxidative stress: Use of APE1 small molecule inhibitors to delineate APE1 functions

Abstract: Oxidative DNA damage has been implicated in a number of central nervous system pathologies. The base excision repair (BER) pathway is one of the most important cellular protection mechanisms that respond to oxidative DNA damage. Human apurinic (apyrimidinic) endonuclease/redox effector factor (APE1/Ref-1 or APE1) is an essential enzyme in the BER pathway and is expressed in both mitotic and post-mitotic cells in humans. In neurons, a reduction of APE1 expression increases chemotherapy-induced cytotoxicity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 49 publications
(112 reference statements)
0
55
0
Order By: Relevance
“…We demonstrated that reducing the activity of the DNA BER pathway by reducing APE1 expression increased the neurotoxicity produced by anticancer treatment, whereas augmenting APE1 activity lessened the neurotoxicity (Vasko et al, 2005(Vasko et al, , 2011Jiang et al, 2008Jiang et al, , 2009. In addition, we demonstrated that APE1's DNA repair function, not its redox signaling function, is crucial for sensory neuron survival and function (Vasko et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…We demonstrated that reducing the activity of the DNA BER pathway by reducing APE1 expression increased the neurotoxicity produced by anticancer treatment, whereas augmenting APE1 activity lessened the neurotoxicity (Vasko et al, 2005(Vasko et al, , 2011Jiang et al, 2008Jiang et al, , 2009. In addition, we demonstrated that APE1's DNA repair function, not its redox signaling function, is crucial for sensory neuron survival and function (Vasko et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…Apurinic/apyrimidinic endonuclease 1/redox factor‐1 (APE1/Ref‐1; henceforth referred to as APE1) is a multifunctional protein that is involved in repairing DNA damage via its endonuclease activity in base excision repair (Fung and Demple, 2005; Izumi et al ., 2005; Jiang et al ., 2009; Kelley et al ., 2014), and using its redox protein–protein signaling function to control the activity of numerous transcription factors such as STAT3, NFκB, AP‐1, p53, and hypoxia‐inducible factor 1α (HIF1α), among others (Cardoso et al ., 2012; Fishel et al ., 2015; Gaiddon et al ., 1999; Jiang et al ., 2010; Kelley et al ., 2012; Lando et al ., 2000; Logsdon et al ., 2016). It also contributes to the removal of damaged bases within RNA (Poletto et al ., 2016; Vascotto et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work from our laboratory, however, we demonstrated that augmenting the base excision repair (BER) pathway by increasing the expression of apurinic/apyrimidinic endonuclease (APE1) is neuroprotective against cisplatin-induced toxicity in isolated sensory neurons [18]. We and others also have shown that cisplatin increases production of reactive oxygen species (ROS) and that oxidative stress may contribute to cisplatin-induced toxicity [1821].…”
Section: Introductionmentioning
confidence: 99%